Women Entrepreneurs and Their Challenges in Business: A Study of Legal Barriers and Digital Empowerment in Kerala - Ranjith Somasundaran Chakkambath; Shamsi Sukumaran; Vyshnavi Biji, (Journal of Women Entrepreneurship & Business Management (e-ISSN: 2583-8210), 2026)
Everyone dreams of a successful business. Traditionally dominated by males, the industry now sees the entrance of many women entrepreneurs who play a major role in contributing to various sectors of the industry. This always generates more jobs and adds to the economy. The research focuses on understanding the challenges faced by an entrepreneur in Kerala. A descriptive cross-sectional study was done using convenience sampling to collected through a structured questionnaire across the State of Kerala, India. The demographic characteristics of the women entrepreneurs were collected to get an insight into their social aspects. The challenges faced by the women in terms of legal red tape hurdles and how they impacted the progress of their business were tested using the Chi-square test. The Exploratory factor analysis gives hints on the various dimensions of challenges that women go through while diving into business or entrepreneurial roles. The findings aim to give an understanding of the current scenario and the future support needed for women entrepreneurs so that they can contribute to the growth of the economy of the region and generate more jobs for the educated youth of this Country. A change of thought from the traditional role of women to women's entrepreneurship is to be encouraged.